Novel visible-light-driven BiFeO3-Bi2WO6nanocomposites toward degradation of dyes - Saranyoo Chaiwichian (2018)
© 2017 Elsevier B.V. The different mole ratios of novel visible-light-driven BiFeO 3 -Bi 2 WO 6 nanocomposites were synthesized by a two-step method, i.e. precipitation followed with hydrothermal process. Advanced characterization techniques such as XRD, TEM, UV–vis DRS, BET-specific surface area, PL, and XPS were used to investigate the physical and optical properties of the as-prepared samples. The photocatalytic activities of pure BiFeO 3 and pure Bi 2 WO 6 catalysts for studying the photodegradation of methylene blue (MB) and rhodamine B (RhB) under visible light irradiation were investigated. The results were compared with BiFeO 3 -Bi 2 WO 6 nanocomposites. The highest photocatalytic activity was the 1:1 mol ratio of BiFeO 3 -Bi 2 WO 6 nanocomposite. The increase of photocatalytic activity of BiFeO 3 -Bi 2 WO 6 nanocomposite was ascribed to the charge transfer through the interface of BiFeO 3 and Bi 2 WO 6 catalysts. This effect helps to reduce the recombination of electron-hole pairs. The combination of the synergistic effect of strong visible absorption edge, the amount of BiFeO 3 and Bi 2 WO 6 , and hydroxyl radicals as the active species was established to enhance photocatalytic efficiency. Based on our investigation, the possible photocatalytic mechanism of BiFeO 3 -Bi 2 WO 6 nanocomposite was proposed.